PELATIHAN ANALISIS PENGAMBILAN KEPUTUSAN BISNIS BAGI SISWA SMA - Sriwati, Sriwati; , Jennifer; Goh, Erica (Jurnal Bakti Masyarakat Indonesia, 2025)
Every company is often faced with various conditions that require decision-making that can have an impact on the sustainability of its business activities. Appropriate and efficient decision-making is one of the main determining factors in the success of a business activity to survive and grow in a competitive business environment. Accurate company financial information and economic trend conditions are needed so that decisions taken are in accordance with company goals. Therefore, the ability to think critically and make decisions is needed in an uncertain and competitive business world. This ability needs to be trained from an early age in order to have a strong foundation when entering the business world. Thus, it is necessary to provide training on business decision making with relevant cost analysis to high school students so that they can understand how important decisions are made based on relevant information. This community service activity was completed in April 2025 and was attended by grade XI students of SMA Santo Kristoforus II. This training began with a presentation of material on the business decision-making process, relevant costs, types of costs based on cost behavior, and examples of the application of business decision-making that are often faced by companies. Then the community service team together with the training participants discussed the case, which had been prepared in advance, with the aim that all participants participate in the decision-making process. After participating in this training, training participants are expected to be able to analyze relevant and irrelevant costs in the business decision-making process so that the decisions taken are in accordance with the company's main objectives.